Developing RDEVS Simulation Models from Textual Specifications - Espertino, Clarisa; Blas, Maria Julia; Gonnet, Silvio (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS); 2022: Anais do IV Workshop em Modelagem e Simulação de Sistemas Intensivos em Software, 2022)
The Routed DEVS (RDEVS) formalism provides a formalization for routing process simulation. This paper presents the mapping between constrained network models obtained from textual specifications of routing processes and RDEVS simulation models implemented in Java. The proposal is part of a work-in-progress intended to develop M&S software tools for the RDEVS formalism using well-known abstractions to get the computational models attached to such abstraction models through conceptual mapping. Then, modelers can have simulation models without needing to codify any routing implementation. Benefits are i) reduction of implementation times and ii) simulation model correctness regarding the RDEVS formalism.